Universal building mixtures on high-module silicate components - Bakhriev Nuritdin Fakhritdinovich; Odilova Gulbakhor Shairovna (Research Parks Publishing LLC, 2020)
The article presents data on the results of research on the development of universal building mixtures. An example of the use of a mixture for laying walls of silicate brick to provide solidity in conditions of high seismic activity is given. Methods for regulating the setting time of unburned alkaline binders on high-modulus silicate components are proposed.